Enhancement security AES algorithm using a modification of transformation ShiftRows and dynamic S-box. (June 2020) - Alamsyah,; Prasetiyo, B; Ardian, M N
Abstract: AES algorithm is a popular encryption algorithm and has a strong resistance to a variety of attacks, especially linear and differential attacks. However, it is necessary to modify the algorithm to improve the performance of the AES algorithm so that the encryption produced (ciphertext) is more resistant from various types of attacks. In this paper, the increased strength of encryption in the AES algorithm uses a modified ShiftRows transformation and dynamic S-box. Modifications to the transformation of ShiftRows are used to simplify the encryption process, while dynamic S-box is used to randomize S-box. The data used in this paper are image data sets. The results of image encryption were tested using histogram analysis, correlation analysis, information entropy, and sensitivity analysis. Based on the test results obtained the ideal range value is 26.76114. This value is better than the results of previous studies.